Causes and consequences of injuries in children in Western Australia - Angalakuditi MV; Angalakuditi N (Dove Medical Press, 2011)
Mallik V Angalakuditi1, Nupur Angalakuditi21Georgia State University, Atlanta, Georgia, 2New York Medical College, Valhalla, New York, USAObjective: To identify the common causes and consequences of pediatric injury-related admission to an Australian children's hospital.Methods: A retrospective study was conducted at a pediatric teaching hospital. Patients , 18 years of age hospitalized between March 1, 2007 and April 30, 2007 were included. Patient medical records were reviewed if an admission diagnosis was injury related. Data collected included date of birth, gender, date of admission, date of discharge, diagnosis, procedure, and causes and outcomes of the injury.Results: A total of 184 patients were admitted as a result of injury during the study period. Of these, one neonate, six infants, 38 toddlers, 111 children, and 28 teenagers were included in this study. The most common cause of injury-related hospital admission was a fall (n = 109, 59%). Other causes of injury included crushing (8%, n = 15), the spilling of fluids (5.4%, n = 10), and bites (4.3%, n = 8). The most common consequence of an injury for children (43/111, 38.7%) and teenagers (12/28, 43%) was bone fracture. However, head injuries were the most common injury in toddlers (11/38, 29%), infants (5/6, 83.3%), and neonates (1/1, 100%). The radius and/ or ulna (36/63, 57%) were the most common bones fractured. The majority (32/37, 86.5%) of patients who suffered head injuries were diagnosed as having a minor injury.Conclusion: The main cause of injury-related admission to the hospital for children was a fall, with the most common consequences being fractures and head injuries.Keywords: injury, falls, head injuries, fractures